Global Energy Efficiency Optimization for Wireless-Powered Massive MIMO Aided Multiway AF Relay Networks - Tan, Fangqing; Lv, Tiejun; Huang, Pingmu (IEEE transactions on signal processing, 2018)
This paper considers a wireless-powered massive multi-input multioutput aided multiway amplify-and-forward relay network, where a relay equipped with massive antennas charges users through energy beamforming and assists with wireless information transmission. For this system, we propose a novel energy-efficient resource allocation scheme for the global energy efficiency (GEE) optimization. In particular, we first derive an accurate closed-form expression of GEE when zero-forcing transceivers are employed in the considered system. Second, based on this analytical expression, we formulate a resource allocation optimization problem for the GEE maximization by jointly optimizing power and time allocation, subject to limited transmit power, time duration, and minimum quality-of-service constraints. Due to the complexity of this nonconvex optimization, a two-layer iterative algorithm is proposed to address the original GEE maximization problem. Numerical results demonstrate the accuracy of our theoretical analysis and the effectiveness of the derived algorithms.